THE IMPLEMENTATION OF AUDIO VISUAL MEDIA TO IMPROVE STUDENTS’ SKILL IN WRITING RECOUNT TEXTS TO THE NINTH GRADE STUDENTS OF SMP SWASTA PABA BINJAI IN THE ACADEMIC YEAR OF 2020/2021 - Sipayung, Ezra Hotdiarta; Prima, Anna Stasya; Prayuda, Meykardo Samuel (Kairos English Language Teaching Journal, 2021)
The objectives of this Classroom Action Research (henceforth, CAR) are to prove that the audio visual media can improve students’ skill in writing recount texts and to describe the students’ responses after being taught with audio visual media. Audio visual media were applied to improve the writing skill of the ninth grade students of SMP Swasta PABA Binjai. After six meetings it could be seen that there is a significant improvement of the students’ audio visual media in writing recount texts. The result of the test showed that the students’ mean score in pre-test is 40,23 with 18 % of students got score ≥ 75, in formative test is 59,09 with 36% of students got score ≥ 75, and in the post test is 72,73 with 73 % of students got score ≥ 75. The percentage students who strongly agree is 60 (66,6%), agree is 30 (33,3%), there is no students choose strongly disagree and disagree. It is suggested that English teachers use audio visual media as an alternative in teaching recount texts to their students.